ANALYSIS OF TIDAL TYPES IN SEMARANG WATERS USING THE ADMIRALTY METHOD: ANALISIS TIPE PASANG SURUT DI PERAIRAN SEMARANG MENGGUNAKAN METODE ADMIRALTY - Az Zahro, Alfiyani; Wahyu, Syafrima; Zahrina Wulansari, Nadia (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
Tides are the rise and fall of sea levels due to the gravitational force of objects in the sky, especially the sun and moon, on the mass of sea water on earth. Semarang waters are located on the north coast of Central Java, which is one of the important coastal areas in Indonesia. This location is located between several large ports and sea trade routes, so information about sea tides is very important for navigation activities and port operations. This research uses tide data in Semarang waters from January to February 2018. The data collection technique was carried out in two ways. The methods used are secondary data and primary data. Secondary data is data obtained from direct surveys carried out by the Hydro Oceanographic Survey Unit Team in certain water areas. Meanwhile, primary data is a complement to secondary data that supports this research, namely using the admiralty method. The research results show that the type of tide in Semarang waters is a single daily tide (diurnal tide) with a formzahl value of 3.94.